2019
DOI: 10.1186/s13765-019-0411-y
|View full text |Cite
|
Sign up to set email alerts
|

Recovery effect of lignans and fermented extracts from Forsythia koreana flowers on pancreatic islets damaged by alloxan in zebrafish (Danio rerio)

Abstract: Repeated column separation yielded four enterolactone type lignans from Forsythia koreana flowers (FKF), whose chemical structures were identified using several spectral technics. FKF MeOH extract (FKFM) and four lignans significantly recovered aloxan induced pancreatic islet in zebrafish. Especially, aglycones, 1 and 3, exhibited relatively higher activity than the lignan glycosides, 2 and 4. Therefore, FKFM was fermented using a Microbacterium esteraromaticum, BGP1, to yield the fermented FKFM (FKFM-BGP1). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The instruments and chemicals used in these experiments were prepared according to previous studies [10][11][12].…”
Section: General Experimental Proceduresmentioning
confidence: 99%
“…The instruments and chemicals used in these experiments were prepared according to previous studies [10][11][12].…”
Section: General Experimental Proceduresmentioning
confidence: 99%
“…Notably, the total content of the major secoiridoids in the extract was very high, 42.4%. It has been reported that the content of secondary metabolites in the floral organs may often be very high when compared with those in other parts of a plant, , indicating that flowers can be a good source of bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The equipment and chemicals used to isolate and identify flavonoids from C. retusus flowers and evaluate their neuroprotective activity were obtained from the literature [32,33,34,35].…”
Section: Methodsmentioning
confidence: 99%